2015
DOI: 10.1200/jco.2015.33.15_suppl.e15541
|View full text |Cite
|
Sign up to set email alerts
|

Is there a gender effect in bladder cancer?: A population-based study of practice and outcomes.

Abstract: Introduction: The incidence of bladder cancer varies by gender. Whether differences exist between women and men in extent of disease, treatment, and outcome is not well-described. We evaluate gender differences in bladder cancer using a population-based cohort. Methods: Electronic records of treatment were linked to the population-based Ontario Cancer Registry to identify all patients with bladder cancer treated with cystectomy or radical radiotherapy (RT) in Ontario between 1994 and 2008. We compare extent of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…27 A few exceptions to the notion of a female survival disadvantage in UBC do exist. 10,28,29 A population-based study from Estonia found men and women to have comparable UBC stage distribution and survival. 28 Similar findings were reported in a Canadian study, which was limited to patients undergoing radical cystectomy or radiotherapy in Ontario.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…27 A few exceptions to the notion of a female survival disadvantage in UBC do exist. 10,28,29 A population-based study from Estonia found men and women to have comparable UBC stage distribution and survival. 28 Similar findings were reported in a Canadian study, which was limited to patients undergoing radical cystectomy or radiotherapy in Ontario.…”
Section: Discussionmentioning
confidence: 99%
“…28 Similar findings were reported in a Canadian study, which was limited to patients undergoing radical cystectomy or radiotherapy in Ontario. 29 The adverse stage distribution suggests more aggressive tumor behavior in women. We found no evidence of this.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that a significantly greater proportion of women are diagnosed at an advanced stage compared with men [24,25]. A large population based study of 5259 patients showed that women were more likely to have muscle-invasive disease at the time of cystectomy [26]. Analysis of all primary UBC patients reported to Swedish National Registry from 1997 to 2011 (30,310 patients) showed a greater proportion of women than men had muscle-invasive disease (stage T2-T4) at presentation (28.6% vs 24.9%, p<0.001) [27].…”
Section: Discussionmentioning
confidence: 99%
“…However, whether this translates into worse survival rates is still debatable. While a metaanalysis of nearly 28,000 patients showed a worse survival in women compared to men [3], several other studies showed no difference in recurrence-free or survival rates [4,5]. Moreover, survival and recurrence data on non-Caucasians patients are scarce.…”
Section: Introductionmentioning
confidence: 99%